Pengembangan Padi Hibrida: Pengalaman dari Asia dan Prospek bagi Indonesia - nFN Ashari; I Wayan Rusastra (Forum penelitian Agro Ekonomi, 2014)
EnglishFood security always occupies top government’s priority in national development due to its huge impact in terms of social, economy, and politics of the country. Regarding the strategic role of food, the policy on increasing food production and farmers' welfare constitute a crucial program, particularly in the Ministry of Agriculture. With the increased demand for food (rice) steadily as well as the rice production levelling off, the government seeks a technological breakthrough, such as hybrid rice introduction. This rice variety is expected to boost production significantly, although its role is still debatable. This paper aims to look at the potential and challenges of hybrid rice development in Indonesia as well as to describe the development in some countries as a comparative study. The result shows both theoretically and factually in some countries, the hybrid rice has a higher potential yield than non-hybrid rice as long as it meets the agronomic requirements. Nevertheless, the development of hybrids (mainly outside of China) still encounters a set of problems, i.e. unstable production, susceptibility to pests and diseases, expensive seed prices, low quality grain, and less-favored rice flavor. Specifically for Indonesia where the hybrid rice is still newly introduced, the hybrid rice development will require a well-planned, gradual, and socialization process. Mass program approaches in hybrid rice which is merely to capture the target oriented, tend to create an ineffectiveness both of output achievement and budget. Agro-ecosystem aspect and the characteristics of farmers in terms of social, economic and cultural sides become a key factor to accomplish the successful hybrid rice development in the future. IndonesianKetahanan pangan selalu menjadi prioritas utama pemerintah dalam pembangunan nasional karena memiliki implikasi yang luas terhadap kondisi sosial, ekonomi, dan politik nasional. Dengan peran yang strategis tersebut kebijakan untuk meningkatkan produksi pangan dan kesejahteraan petani selalu menjadi agenda penting, terutama di Kementerian Pertanian. Dengan terus meningkatnya permintaan akan pangan (beras) serta kecenderungan terjadinya pelandaian produksi maka pemerintah berupaya melakukan sejumlah terobosan di antaranya dengan memperkenalkan padi hibrida. Varietas ini diharapkan mampu mendongkrak produksi beras secara nyata walaupun peran tersebut masih menimbulkan perdebatan. Paper ini bertujuan melihat potensi dan tantangan pengembangan padi hibrida di Indonesia sekaligus memaparkan kondisi pengembangan di beberapa negara sebagai studi perbandingan. Hasil studi menunjukkan bahwa secara teori dan faktual di beberapa negara lain padi hibrida memiliki potensi hasil lebih tinggi dari inbrida asalkan memenuhi persyaratan agronomis. Namun demikian, pengembangan hibrida di luar negara Cina secara umum masih menghadapi sejumlah kendala di antaranya ketidakstabilitan produksi, kerentanan terhadap hama penyakit, harga benih yang mahal, kualitas gabah yang rendah, dan rasa nasi yang belum sesuai dengan keinginan konsumen. Dalam konteks Indonesia, di mana padi hibrida masih menjadi komoditas yang relatif baru (inovasi), maka dalam pengembangan memerlukan tahapan-tahapan yang terencana dan proses sosialisasi yang matang. Massalisasi padi hibrida melalui program dan hanya berorientasi pada target realisasi menyebabkan ketidakefektifan baik dari sisi capaian output maupun anggaran. Kondisi agroekosistem serta karakteristik petani baik aspek sosial, ekonomi dan budaya menjadi faktor kunci bagi keberhasilan pengembangan padi hibrida ke depan.